Major advances in bioengineered heart implants.
'Tissue engineering' (TE) and 'regenerative medicine' (RM) will be at the core of heart surgery in the future. An EU initiative generated a platform of expertise to supply top-class training for researchers to enable development of bioengineered cardiovascular implants.